Nanotechnology and its Role in the Advancement of Horticultural Crops: A Scientific Article - Al-Dulaimi, Fatin Hussein; Al-Najjar, Mohammed AbdAlameer Hassan; Aliwy, Sukeyna Abbas; Fadel, Wasen Fawzy (Journal of agricultural, environmental and veterinary sciences, 2025)
Nitrogen fertilizers, particularly urea, are among the most widely used agricultural inputs due to their high nitrogen content and easy availability. However, one of their major drawbacks is their rapid hydrolysis in moist soils, leading to ammonia volatilization and nitrogen loss. This process results in serious environmental consequences, including eutrophication of water bodies and the emission of nitrous oxide a major greenhouse gas associated with agricultural activities. Similarly, conventional phosphate and potassium fertilizers suffer from issues such as nutrient fixation in the soil and reduced bioavailability to plants, which lower nutrient use efficiency and compel farmers to increase fertilizer application rates to maintain productivity. In low-income regions, where pollution levels are rising and food security remains fragile, the high cost and repeated application of these fertilizers pose a substantial economic burden, negatively affecting the sustainability of agricultural production.In response to these challenges, recent studies have focused on developing advanced agricultural technologies, notably the application of nanotechnology in fertilization. This includes the development of slow-release nano-fertilizers such as nano-urea, nano-phosphate, nano-zinc, and nano-iron, which offer higher nutrient use efficiency, reduced nutrient losses, improved soil fertility, and minimized environmental impacts. Such innovations represent a promising approach toward achieving sustainable and environmentally friendly agriculture.
Keywords: Nanotechnology; Nano crops; Agro-Nanotechnology; Nano fertilizers; Nitrogen use efficiency; Sustainable production